Phase I study of onapristone, a type I antiprogestin, in female patients with previously treated recurrent or metastatic progesterone receptor-expressing cancers - Cottu, Paul H.; Bonneterre, Jacques; Varga, Andrea; Campone, Mario; Leary, Alexandra; Floquet, Anne; Berton-Rigaud, Dominique; Sablin, Marie-Paule; Lesoin, Anne; Rezai, Keyvan; Lokiec, François M.; Lhomme, Catherine; et al. (PLOS ONE, 2018)
Introduction Onapristone is a type I progesterone receptor (PR) antagonist, which prevents PR- mediated DNA transcription. Onapristone is active in multiple preclinical models and two prior studies demonstrated promising activity in patients with breast cancer. We conducted a study of extended release (ER) Onapristone to determine a recommended dose and explore the role of transcriptionally-activated PR (APR), detected as an aggregated subnuclear distribution pattern, as a predictive biomarker. Methods An open-label, multicenter, randomized, parallel-group, phase 1 study (target n = 60; NCT02052128) included female patients ≥18 years with PRpos tumors. APR analysis was performed on archival tumor tissue. Patients were randomized to five cohorts of extended release (ER) onapristone tablets 10, 20, 30, 40 or 50 mg BID, or immediate release 100 mg QD until progressive disease or intolerability. Primary endpoint was to identify the recommended phase 2 dose. Secondary endpoints included safety, clinical benefit and pharmacokinetics. Results The phase 1 dose escalation component of the study is complete (n = 52). Tumor diagnosis included: endometrial carcinoma 12; breast cancer 20; ovarian cancer 13; other 7. Median age was 64 (36–84). No dose limiting toxicity was observed with reported liver function test elevation related only to liver metastases. The RP2D was 50 mg ER BID. Median therapy duration was 8 weeks (range 2–44), and 9 patients had clinical benefit ≥24 weeks, including 2 patients with APRpos endometrial carcinoma. Conclusion Clinical benefit with excellent tolerance was seen in heavily pretreated patients with endometrial, ovarian and breast cancer. The data support the development of Onapristone in endometrial endometrioid cancer. Onapristone should also be evaluated in ovarian and breast cancers along with APR immunohistochemistry validation.